THE ROLE OF ISLAMIC SOCIAL FINANCE IN THE PREPARATION OF MUBALLIGH CADRES IN PESANTREN - Muhammad Choirin; Dion Saputra Arbi; Asep Supyadillah; Fakhrul Adabi Abdul Kadir (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
This paper investigates the nexus between Islamic social finance and pesantren, focusing on its implications for the preparation of muballigh cadres. Grounded in the rich Islamic tradition, pesantren serve as pivotal institutions for molding future leaders deeply rooted in Islamic teachings. This study addresses a significant research gap by examining the specific impact of Islamic social finance within pesantren on the preparation of muballigh cadres, filling a void in the existing literature. Through qualitative analysis, it investigates how mechanisms such as waqf, zakat, and sadaqah influence the training of future Islamic preachers within these institutions. The findings highlight the role of Islamic social finance in sustaining pesantren operations, fostering community development, and shaping the ethical, social, and economic dimensions of muballigh cadres' preparation. Theoretically, this study expands the discourse on Islamic social finance by demonstrating its relevance and application in educational and leadership contexts within pesantren. It also offers practical recommendations for policymakers and practitioners to optimize these mechanisms in advancing the role of pesantren in Islamic education and community development.